Vergleich von Methoden zur Pulsationsmessung an innenmischenden Zweistoffdüsen. Issue 10 (2nd August 2013) - Schlinge, Britta; Schröder, Jewe; Gaukel, Volker; Schuchmann, Heike P.; Walzel, Peter; Kraume, Matthias
<x xml:space="preserve">Abstract</x> In the application of internal‐mixing twin‐fluid atomizers, a pulsation of the spray flow can occur. In this case, the temporal and spatial distributions of drop size and drop number are unsteady. This has a negative impact on subsequent processes and is therefore unwanted. The pulsation needs to be detected and quantified in order to identify parameters causing pulsation of the spray. Three measurement techniques have been investigated: an optical method applying high speed imaging, an acoustical method recording the fluctuation of the emissions at the atomizer orifice and a method detecting the fluctuation of the drop size distribution measured by laser diffraction spectroscopy.